"Sweating meteorites"—Water‐soluble salts and temperature variation in ordinary chondrites and soil from the hot desert of Oman. (24th October 2013) - Zurfluh, Florian J.; Hofmann, Beda A.; Gnos, Edwin; Eggenberger, Urs
Abstract: The common appearance of hygroscopic brine ("sweating") on ordinary chondrites (OCs) from Oman during storage under room conditions initiated a study on the role of water‐soluble salts on the weathering of OCs. Analyses of leachates from OCs and soils, combined with petrography of alteration features and a 11‐month record of in situ meteorite and soil temperatures, are used to evaluate the role of salts in OC weathering. Main soluble ions in soils are Ca 2+, SO4 2−, HCO3 −, Na +, and Cl −, while OC leachates are dominated by Mg 2+ (from meteoritic olivine), Ca 2+ (from soil), Cl − (from soil), SO4 2− (from meteoritic troilite and soil), and iron (meteoritic). "Sweating meteorites" mainly contain Mg 2+ and Cl − . The median Na/Cl mass ratio of leachates changes from 0.65 in soils to 0.07 in meteorites, indicating the precipitation of a Na‐rich phase or loss of an efflorescent Na‐salt. The total concentrations of water‐soluble ions in bulk OCs ranges from 600 to 9000 μg g −1 (median 2500 μg g −1 ) as compared to 187–14140 μg g −1 in soils (median 1148 μg g −1 ). Soil salts dissolved by rain water are soaked up by meteorites by capillary forces. Daily heating (up to 66.3 °C) and cooling of the meteorites cause a pumping effect, resulting in a strong concentration of soluble ions in meteorites over time. The concentrations of water‐soluble ions in meteorites, which are complex mixtures of ions from the soil and from oxidation and hydrolysis of meteoritic material, depend on the degree of weathering and are highest at W3. Input of soil contaminants generally dominates over the ions mobilized from meteorites. Silicate hydrolysis preferentially affects olivine and is enhanced by sulfide oxidation, producing local acidic conditions as evidenced by jarosite. Plagioclase weathering is negligible. After completion of troilite oxidation, the rate of chemical weathering slows down with continuing Ca‐sulfate contamination.